A STUDY ON STUDENTS’ MORPHOLOGICAL AWARENESS ABILITY OF THE FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM UNIVERSITAS RIAU - Putri Khairunnisa; Syofia Delfi; Supriusman Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was aimed to find out the ability of the fourth semester students’ morphological awareness in English Study Program, Universitas Riau. The population of this research was the fourth semester students. The number of sample was 23 students selected randomly from 3 classes (A Class, B Class, and C Class) by using cluster random sampling technique. The instrument used to collect the data was a written test in the form of multiple choices with 55 questions based on the indicators of morphological awareness stated by Ken Apel (2014). The test instrument consist of four parts which cover the components of morphological awareness namely spoken form of morphemes (allomorph), meaning and grammatical changes, manner of affixes (orthography), and relation between base words and its derived and inflected forms. The data were analyzed by using a formula made by Wayan and Sumartana (1986) and then classified into five levels of ability: very poor, poor, mediocre, good and excellent by using classification made by Harris (1969). Based on the findings of this research, it was found that the students’ morphological awareness ability of the fourth semester students was in a good level with the mean score 63. The implication of this research is that the fourth semester students are in a good level of morphological awareness ability.Key Words: Students’ Morphological Awareness, Students’ ability.